Trends in international migrant stock... -2008- (UN New YorkUS, 2009)
Contains estimates on the number of international migrants in each country or area of the world as of 1 July of the years 1960, 1965, 1970, 1975, 1980, 1985, 1990, 1995, 2000, 2005, and 2010. Includes also information on refugees and the status of migrants.
Keywords: MIGRANTS